Just remembering : rhetorics of genocide remembrance and sociopolitical judgment - Tumolo, Michael Warren (The Fairleigh Dickinson University Press series in communication studies, 2015)
Acknowledgments -- Just remembering : rhetorics of genocide remembrance and sociopolitical judgment -- Genocide and memory politics : an "Armenian genocide" resolution, a staging ground for war, and "pragmatic nullification" -- Nullification in international memory discourse : tracing the capture of Adolf Eichmann from legal outrage to moral consciousness -- Consequences of memory : a bureaucrat, a monster, and sociopolitical judgment -- Consequential remembrance : president's commission on the holocaust -- A commitment to preventing recurrence : the "living memorial" and the committee on conscience -- About the author